Assessment of left atrial function by MRI myocardial feature tracking. Issue 2 (28th January 2015) - Evin, Morgane; Cluzel, Philippe; Lamy, Jerôme; Rosenbaum, David; Kusmia, Slawek; Defrance, Carine; Soulat, Gilles; Mousseaux, Elie; Roux, Charles; Clement, Karine; Hatem, Stéphane N.; Redheuil, Alban; et al.
<x xml:space="preserve">Abstract</x> Background Left atrium (LA) volumes and function are predictors of cardiovascular events. Because LA function cannot be assessed from cardiovascular magnetic resonance imaging (MRI) using the well‐established left ventricular tagging techniques, we hypothesized that adequate feature tracking (FT) applied to conventional cine MRI data could characterize LA function accurately. Methods We studied 10 young (28 ± 7 years) and 10 elderly (64 ± 6 years) healthy subjects, as well as 20 patients with moderate to severe aortic valve stenosis (AVS; 73 ± 15 years, effective aortic valve area: 0.67 ± 0.36 cm2). MRI cine two‐, three‐, and four‐chamber views were analyzed using a newly proposed FT method based on spatial correlation and endocardial detection resulting in: regional and global longitudinal strain and strain rate, radial motion fraction and relative velocity for the three LA motion phases including reservoir, conduit, and LA contraction. Results FT reliability was indicated by a good overlap between tracking results and manual LA endocardial borders, the low error for comparison against theoretical strains introduced in a synthetic phantom and the good inter‐observer reproducibility (coefficient of variation < 15%). While all LA functional parameters were significantly impaired in AVS patients (p < 0.04), subclinical age‐related variations induced a decreasing trend on all LA parameters but were significant only for radial conduit function parameters (p < 0.03). Finally, LA functional parameters characterized LA alteration in AVS with higher sensitivity than conventional LA volumetric parameters. Conclusions Left atrial FT is feasible on MRI cine images and its addition to conventional analysis tools might enhance the diagnosis value of MRI in many heart diseases. J. Magn. Reson. Imaging 2015;42:379–389.